2016
DOI: 10.1002/lary.25847
|View full text |Cite
|
Sign up to set email alerts
|

Hyoid surgery alone for obstructive sleep apnea: A systematic review and meta-analysis

Abstract: NA Laryngoscope, 126:1702-1708, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 28 publications
2
27
1
1
Order By: Relevance
“…HTP, which has proven efficacy, was widely implemented, with several modifications and reports presented. 2-8,11-16,18 The present study supports the concept that surgeries at the HB might widen and support the hypopharyngeal airway space, thus preventing transversal collapse. 1,5,8,10-12…”
Section: Discussionsupporting
confidence: 86%
“…HTP, which has proven efficacy, was widely implemented, with several modifications and reports presented. 2-8,11-16,18 The present study supports the concept that surgeries at the HB might widen and support the hypopharyngeal airway space, thus preventing transversal collapse. 1,5,8,10-12…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with a recent meta-analysis, which showed that AHI is reduced by 38.3% after HMS for OSA. 18 In our study, ESS was unchanged postoperatively; however, the mean preoperative ESS score (8.2) was already within the normal range and therefore less likely to change.…”
Section: Discussioncontrasting
confidence: 47%
“…The effectiveness of sleep surgery in treating OSA remains controversial 34,47 . Several surgical procedures have been proposed, including nasal surgery, 48,49 uvulopalatopharyngoplasty, 50 pharyngeal surgery, 51 tongue base surgery, 52 multilevel surgery, 53,54 maxillomandibular advancement, 55,56 hyoid surgery, 57 tracheostomy, 58 and hypoglossal nerve stimulation 59,60 . Studies have described disparities in the outcomes of different surgical procedures 61 ; accordingly, the identification of predictive factors for poor outcomes and appropriate selection of patients are critical 62,63 …”
Section: Discussionmentioning
confidence: 99%